Valuation of South China Tiger conservation in Wangcheng Park, China: a discrete choice experiment accounting for attribute nonattendance - Li, Yuanyuan; W. Mohamad, Wan Norhidayah; Samdin, Zaiton (Malque Publishing, 2024)
The South China tiger is endemic to China and has been evaluated as critically endangered (possible extinct in the wild) by IUCN since 2008, which resulted in distributing them zoos in China to conserve its species before finding a suitable area in the wild and bringing them back to the roar. Economic valuations of endangered species can help policymakers develop more efficient conservation strategies. Discrete choice experiment is becoming more appropriate, allowing the valuation of specific attributes of environmental goods and services. However, ignoring the attribute nonattendance issue in the DCE analysis yields biased estimates and erroneous potential recommendations. In this study, multinomial logit and mixed logit models are estimated to explore visitors' preferences and the implications of attribute nonattendance issues by using supplementary questions. The results indicate that the number of SCT is the most preferred attribute, followed by size of the natural habitat, frequency of the conservation campaigns, and level of the conservation institutions. Moreover, the results also show that accounting for attribute nonattendance does not change the relative ranking order of visitors' preferences in both multinomial and mixed logit models, while yielding higher WTP estimates in both models. These results shed more light on the importance of attribute nonattendance in future DCE analyses.